INDIAN COSTUS IN ISLAMIC, AYURVEDA, TCM AND MODERN MEDICINE, A REVIEW ON ANTIMICROBIAL ACTION - Fathy Hussein, Emad Ahmed; Hassan, Shahira; Bayomy, Mohamed F.F; Shaikh, Tabish Ishaq; Helmy Saleh, Ahmed (International Journal of Islamic and Complementary Medicine, 2024)
Indian Costus species has been mentioned as an herbal remedy for infections in Islamic, Ayurveda and Traditional Chinese Medicine (TCM) literature as well. Using the Indian costus to treat disease is one of the cross-cultural practices, just like cupping therapy and meditation. This would mean that it is safe and beneficial. In the saying (Hadith) of the prophet of Islam, it was prescribed to treat pharyngitis and pleurisy (Ahmad et al., 2009). In TCM, Costus root (Guang Mu Xiang) powder is used to treat gastroenteritis and tenesmus (Nystrom, 2015). In Ayurveda, it is used as a spasmolytic and antiparasitic for intestinal disease (Pandey et al., 2007). Among the pharmacological benefits of costus is the antimicrobial effect. This includes the antibacterial, antiviral, antifungal and antiparasitic action of the substances to be discussed here. We did a focus on the antimicrobial effect in the three systems, compared and concluded findings through modern medicine to verify the evidence here.